A low‐profile microwave device integrating dual‐polarized filtering antenna and lowpass filter. Issue 2 (7th November 2021) - Guo, Jiayin; Liu, Feng; Ni, Chao; Zhao, Luyu; Li, Yapeng; Wu, Wei‐Jun; Yin, Yingzeng
Abstract: This paper presents a low profile, multifunctional microwave device, which behaves either as a dual‐polarized filtering antenna or as a lowpass filter. For the dual‐polarized filtering antenna, two introduced quarter‐wavelength open‐circuit stubs can generate a radiation null at the lower frequency stopband to obtain good frequency selectivity. Moreover, to improve the out‐of‐band radiation suppression level at high frequencies, the C‐shaped short‐circuit stubs and U‐shaped metal strips are loaded at feeding structures. In the case of the filter, the feeding network and part of the patchwork together to form a lowpass filter. The overall height of the designed microwave device is only 0.05 wavelengths at 2.6 GHz. The results show that the average gain is 8.09 ± 0.54 dBi in the antenna frequency band with out‐of‐band gain suppression level of 25.1 dB. Moreover, when the device act as a lowpass filter, the insertion loss between the two ports is less than 0.7 dB at the lower working band.